An improved phase difference detection method for a Coriolis flowmeter - Huang, Lei (Measurement : journal of the International Measurement Confederation, 2021)
•The accurate model of Coriolis flowmeter was obtained.•The new phase difference calculation method did not need whole period sampling.•The relationship between calculation amount and accuracy was analyzed.•Experiments of different flow rates and temperatures were carried out. To detect the phase difference of two vibration signals in a Coriolis flowmeter, the commonly used methods include the zero crossing phase detection method, the correlation function method and the Fourier transform method. However, these methods are subject to low accuracy, entire-cycle sampling and excessive calculation. To solve these problems, a Coriolis flowmeter experimental system was initially modeled, and then a phase difference detection method was built based on least squares and curve fitting. The results showed that this method could reduce the amount of calculation significantly without reducing the detection accuracy or adjusting the entire-cycle sampling. A simulation and a single-phase flow experiment indicated that this method was simple, practical and efficient, and it provided a new method for data processing with a Coriolis flowmeter.